E-LEARNING AND LEARNING INTEREST TOWARDS THE STUDENTS’ ENGLISH ACHIEVEMENT - Ana Theriana; Dewi Kartika Sari; Etty Pratiwi (Universitas PGRI Palembang, 2021)
This research aimed to determine that E-Learning Based Learning and students’ interest in learning can make a significant difference in increasing learning achievement. Researchers took two research samples. The first group was taught using E-Learning and the second using conventgional (face-to-face). To collect data, both groups were given a speech test and an interest in learning questionnaire. For E-Learning, data had collected using the Zoom application which is evaluated by the researcher using a questionnaire consisting of 2 parts, namely fluency and understanding. Meanwhile, students' interest in learning was evaluated using a questionnaire. In E-Learning, lecturers and students consider several topics given by the lecturer. After that, they decide what type of product they produced on their project as a final result, such as: Visual Learning Media, Audio Learning Media and Audiovisual Learning Media. The results showed that (1) there was a significant difference in both student interest in learning (t = 8.822, p <.000) and achievement (t = 7.911, p <.000) from the experimental group after being taught using E-Learning, (2 ) the contribution to the improvement of student learning achievement was 98.7% and interest in learning was 92.1%. So it can be concluded that E-Learning-based learning has an effect on student achievement and interest in learning.